2013
DOI: 10.1017/s1368980013001316
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of fruit and vegetable intake in countries of the former Soviet Union

Abstract: Objective: To assess how the frequency of low fruit and vegetable consumption has changed in countries of the former Soviet Union (FSU) between 2001 and 2010 and to identify factors associated with low consumption. Design: Cross-sectional surveys. A standard questionnaire was administered at both time points to examine fruit and vegetable consumption frequency. Logistic regression analysis was used to examine the relationship between demographic, socio-economic and health behavioural variables and low fruit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
3
24
0
1
Order By: Relevance
“…Our results also suggest that participants with higher income and education level are more likely to have a positive opinion of the healthiness of their diet as was previously observed (Hill et al 2006;Canadian Council of Food and Nutrition 2008;Loftfield et al 2015). These differences in the perception of diet healthiness according to sociodemographic characteristics corroborate the results from numerous studies showing significantly healthier diet in women (Wardle et al 2000;Garriguet 2009;Dehghan et al 2011;Abe et al 2013;Aggarwal et al 2014;Goryakin et al 2015;Swan et al 2015), older individuals (Beydoun and Wang 2008;Dehghan et al 2011;Aggarwal et al 2014;Swan et al 2015), and people with higher income (Kamphuis et al 2006;Beydoun and Wang 2008;Garriguet 2009;Abe et al 2013;Aggarwal et al 2014;Goryakin et al 2015;Swan et al 2015) or education level (Wardle et al 2000;Beydoun and Wang 2008;Garriguet 2009;Dehghan et al 2011;Abe et al 2013;Aggarwal et al 2014;Goryakin et al 2015). Our results also showed that BMI decreased as the self-rated diet quality increased, as observed elsewhere (Loftfield et al 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Our results also suggest that participants with higher income and education level are more likely to have a positive opinion of the healthiness of their diet as was previously observed (Hill et al 2006;Canadian Council of Food and Nutrition 2008;Loftfield et al 2015). These differences in the perception of diet healthiness according to sociodemographic characteristics corroborate the results from numerous studies showing significantly healthier diet in women (Wardle et al 2000;Garriguet 2009;Dehghan et al 2011;Abe et al 2013;Aggarwal et al 2014;Goryakin et al 2015;Swan et al 2015), older individuals (Beydoun and Wang 2008;Dehghan et al 2011;Aggarwal et al 2014;Swan et al 2015), and people with higher income (Kamphuis et al 2006;Beydoun and Wang 2008;Garriguet 2009;Abe et al 2013;Aggarwal et al 2014;Goryakin et al 2015;Swan et al 2015) or education level (Wardle et al 2000;Beydoun and Wang 2008;Garriguet 2009;Dehghan et al 2011;Abe et al 2013;Aggarwal et al 2014;Goryakin et al 2015). Our results also showed that BMI decreased as the self-rated diet quality increased, as observed elsewhere (Loftfield et al 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Dietary questionnaire Finbalt Health Monitor (66) 4 (Estonia, Finland, Latvia, Lithuania) FFQ Finnish and Russian Karelia study (67) (126,127) HTT (71) 9 (Armenia, Azerbaijan, Belarus, Georgia, Kazakhstan, Kyrgyzstan, Moldova, Russia, Ukraine)…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…Hupkens et al (72) 3 (Belgium, Netherlands, Germany) FFQ X (128) I.Family Project (50,73,74) 8 (Belgium, Cyprus, Estonia, Germany, Hungary, Italy, Spain, Sweden) Diet questionnaire (FFQ) which was included as part of the parent questionnaire X Online 24-HDR (SACANA) IHBS (75) 17 (Austria, Denmark, England, Finland, France, Germany, Greece, Iceland, Ireland, Netherlands, Norway, Poland, Portugal, Scotland, Spain, Sweden, Switzerland) FFQ X IMMIDIET (76) 3 (Italy, Belgium, England) EPIC-Italian FFQ X (39,129) EPIC-UK FFQ Specifically developed Belgian FFQ Kolarzyk et al (48) 4 (Poland, Belarus, Russia, Lithuania) FFQ X LiVicordia (77) 2 (Lithuania, Sweden) 24-HDR LLH (71) 8 (Armenia, Belarus, Georgia, Kazakhstan, Kyrgyzstan, Moldova, Russia, Ukraine) FFQ MEDIS (78) 2 (Cyprus, Greece) FFQ X (138) MGSD (79) 6 (Greece, Italy, Algeria, Bulgaria, Egypt, Yugoslavia (only diabetics in Yugoslavia)) Dietary history method using questionnaire X (79) NORBAGREEN (41,80) 8 (Norway, Denmark, Sweden, Finland, Latvia, Lithuania, Estonia, Iceland) FFQ X (80) O'Neill et al (82) 5 (UK, Republic of Ireland, Spain, France, Netherlands) FFQ X Parfitt et al (83) 2 (England, Italy) 5-7 d record PRIME (84) 2 (Northern Ireland, France) FFQ X PRO GREENS (85) 10 (Austria, Belgium, Denmark, Iceland, Netherlands, Norway, Portugal, Spain, Sweden, Finland)…”
Section: Ffqmentioning
confidence: 99%
“…Cockerham [ 22 ] described dietary behavior as an important unhealthy lifestyle factor in Russia, especially among men. Specifically, fruit and vegetable consumption was insufficient in almost all former Soviet Union countries; the percentage of people consuming fruits daily increased (from 14.9% to 31.2%) and that of people consuming vegetables daily decreased (from 44.6% to 35.5%) during the period 2001–2010, although the quantity of consumption was not examined [ 23 ], preventing evaluation using the World Health Organization’s (WHO’s) recommendations. In the late 1990s, poverty was the main reason for insufficient intake of calories, protein, vegetables, and fruits in the elderly population.…”
Section: Introductionmentioning
confidence: 99%